Current developments of metal- and metalloid-based quinoline compounds as leishmanicidal agents - Del Carpio, Edgar; Hernández, Lino; Lubes, Vito; Jourdan, Francisco; Cerecetto, Hugo; Scalese, Gonzalo; Gambino, Dinorah; Romero, Angel H. (Frontiers in Chemistry, 2025)
The quinoline moiety represents an important scaffold for the development of leishmanicidal agents. In particular, its hybridization with metal/metalloids has generated highly active compounds that are, in some cases, highly selective against leishmaniasis models. The existing leishmanicidal metal-/metalloid-quinoline compounds are mainly based on the following: (i) coordination compounds based on 8-hydroxyquinolinate; (ii) metallocene derivatives; (iii) N-heterocyclic carbene (NHC) complexes featuring a quinoline moiety. This mini-review summarizes the reported cases of leishmanicidal metal and metalloid-based quinoline compounds for each group (i–iii), focusing on the structure-property relationship from in vitro Leishmania models and mechanisms of action, in vivo experiments, and pharmacokinetic data, if available. This paper aims to describe the state of the art of inorganic medicinal chemistry for the development of selective and potent leishmanicidal agents using the quinoline moiety.